Quality tools for improvements of the production process in microenterprise: The implementation of improvements in the production process through the quality tool: Case study in a regional flour packer in Manaus - Lima , Janderson Costa de; Barros , Sâmara Alexandra de Lima; Amorim , Marcos Bandeira; Florentino , Gelson Dias (Seven Editora, 2023)
This research aimed to optimize the packaging process, mapping the operational difficulties of a company that packs and markets regional flour in Manaus. It presented a better theoretical understanding of quality tools: Ishikawa Diagram and 5W2H. As well as bringing a case study of its application. To achieve these objectives, the work was based on simple and low-cost changes. By analyzing the daily routine of the company's production sector, through action research with its employees. Classified as a qualitative method that seeks to understand the problems and contexts involved through data collection, such as interviews, participant observation and document analysis, Denise Filippo (2011 p.452). It was possible to identify some obstacles with regard to planning, control and process modes that, over the years, brought a lot of damage to the business. Specifically, the investigation seeks to identify and create action plans, with the purpose of solving the problems that generate delays in the elaboration of works in the production sector, improving the operational performance of the company's production. As a result, it was found that the tools, in general, helped the production sector to better organize its work routine, as well as bringing suggestions for improvements to problems found during this study, such as: the improvement of productivity rates, better redistribution of tasks and standardization of services. DOI:https://doi.org/10.56238/alookdevelopv1-152